2020
DOI: 10.3390/genes11010090
|View full text |Cite
|
Sign up to set email alerts
|

Unwinding BRAHMA Functions in Plants

Abstract: The ATP-dependent Switch/Sucrose non-fermenting (SWI/SNF) chromatin remodeling complex (CRC) regulates the transcription of many genes by destabilizing interactions between DNA and histones. In plants, BRAHMA (BRM), one of the two catalytic ATPase subunits of the complex, is the closest homolog of the yeast and animal SWI2/SNF2 ATPases. We summarize here the advances describing the roles of BRM in plant development as well as its recently reported chromatin-independent role in pri-miRNA processing in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…However, the molecular mechanisms of how sugars and auxin mediated transcriptional changes are linked to growth and developmental responses are poorly understood. In recent years, compelling studies have shown that in addition to transcription factors, chromatin and epigenetic based mechanisms are important regulators of transcriptional changes underlying growth and developmental plasticity (Huai et al 2018; Jia et al 2020; Li et al 2015; Thouly et al 2020; Xi et al 2020). Mediator complexes are also central players of the transcriptional machinery whose function is to recruit transcription factors and cofactors to the site of active transcription (Agrawal et al 2021).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, the molecular mechanisms of how sugars and auxin mediated transcriptional changes are linked to growth and developmental responses are poorly understood. In recent years, compelling studies have shown that in addition to transcription factors, chromatin and epigenetic based mechanisms are important regulators of transcriptional changes underlying growth and developmental plasticity (Huai et al 2018; Jia et al 2020; Li et al 2015; Thouly et al 2020; Xi et al 2020). Mediator complexes are also central players of the transcriptional machinery whose function is to recruit transcription factors and cofactors to the site of active transcription (Agrawal et al 2021).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…A typical SWI/SNF complexes have been found to be vital for plant development and responses to environmental stimuli, mainly through the transcriptional regulation of key genes (Han et al, 2015;Li et al, 2016;Archacki et al, 2017). These complexes are required for leaf development, embryo development, root stem cell niche maintenance, flowering time regulation, cotyledon separation, the juvenile-to-adult phase transition, photomorphogenesis, inflorescence and flower development, and abiotic stress and hormone responses (Hurtado et al, 2006;Archacki et al, 2013Archacki et al, , 2009Farrona et al, 2004;Li et al, 2015;Yang et al, 2015;Sarnowska et al, 2016;Xu et al, 2016;Thouly et al, 2020;Wagner and Meyerowitz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional regulators play essential roles in transcriptional reprogramming during development, physiological and stress responses. The SNF2 protein is a critical component of the chromatin remodeling complex [ 68 ]. The involvement of SNF2 has been shown in response to abiotic stress.…”
Section: Discussionmentioning
confidence: 99%